Clearable black phosphorus nanoconjugate for targeted cancer phototheranostics - Jana, Deblin (2021)
Therapeutic efficacy of synergistic photodynamic therapy (PDT) and photothermal therapy (PTT) is limited by complex conjugation chemistry, absorption wavelength mismatch and inadequate biodegradability of the PDT-PTT agents. Herein, we designed biocompatible copper sulfide nanodot anchored folic acid-modified black phosphorus nanosheets (BP-CuS-FA) to overcome these limitations, consequently enhancing the therapeutic efficiency of PDT-PTT. In vitro and in vivo assays reveal good biocompatibility and commendable tumor inhibition efficacy of the BP-CuS-FA nanoconjugate owing to synergistic PTT-PDT mediated by near-infrared laser irradiation. Importantly, folic acid unit could target folate receptor overexpressed cancer cells, leading to enhanced cellular uptake of BP-CuS-FA. BP-CuS-FA also exhibits significant contrast effect for photoacoustic imaging, permitting its in vivo tracking. The photodegradable character of BP-CuS-FA is associated with better renal clearance after the antitumor therapy in vivo. The present research may facilitate further development on straightforward approaches for targeted and imaging-guided synergistic PDT-PTT of cancer.